Cellular Functions of RNA-Binding Motif Protein 3 (RBM3): Clues in Hypothermia, Cancer Biology and Apoptosis - I. M. Al-Astal, Heyam; Massad, Maram; AlMatar, Manaf; Ekal, Harith (Protein and Peptide Letters, 2016)
Cell rapidly adapts to the harsh environment under certain conditions such as hypothermia and stress via activity of certain specific cold-shock proteins. Two cold shock proteins, RNA-binding motif protein 3 (RBM3) and coldinducible RNA binding proteins (CIRP), have been unveiled in human cells. RBM3, which is able to regulate their expression at the level of translation by binding to different transcripts, allows the cell to respond rapidly to environmental signals. Additionally, expression of RBM3 is induced under mild to moderate hypothermia, and stress. Stress-response pathways play an essential role in cancer. In different types of cancer, RBM3 is up regulated and correlated with favourable clinic- pathological features. RBM3 plays certain functions such as anti-apoptotic, cell proliferation enhancement, and a proto-oncogene function. Furthermore, Hypothermia-induced neuroprotection up- regulates RBM3 in neuronal cells. In this review, the multifunctional nature of RMB3 is outlined through summarizing the evidences from in vitro and in vivo studies.
Keywords: RNA-binding motif protein 3 (RMB3)